Dapagliflozin and Silymarin Ameliorate Cisplatin-Induced Nephrotoxicity via Nrf2/HO-1 Upregulation: A Preclinical Mechanistic Study - Shakta Mani Satyam; Laxminarayana Kurady Bairy; Abdul Rehman; Anuradha Asokan Nair; Mohamed Farook; Nirmal Nachiketh Binu; Sofiya Khan; Mohamed Yehya; Mohammed Moin Khan (Sci)
This study evaluated the nephroprotective potential of dapagliflozin and silymarin, alone and in combination, against cisplatin-induced kidney damage in female Wistar rats. Cisplatin was administered at 3 mg/kg weekly to all groups except the normal controls, with treatments of silymarin (50 mg/kg/day), dapagliflozin (0.9 mg/kg/day), or both for 45 days. Dapagliflozin significantly reduced uric acid, the urea-to-creatinine ratio, and serum urea levels compared to nephrotoxic controls, while combination therapy showed further improvements. Both agents decreased inflammatory markers like TNF-alpha, IL-6, and IL-1 beta, with enhanced effects in combination. Oxidative stress markers, including nitrite and 4-HNE, were lowered, and antioxidant enzyme activities (catalase, SOD, and GSH-Px) were increased by dapagliflozin and silymarin, with the combined treatment yielding the most substantial improvements. Molecular analysis revealed elevated Nrf2 and HO-1 levels, which are critical for oxidative stress mitigation, particularly with combination therapy. Histologically, combination therapy preserved renal structure, closely resembling normal controls, while dapagliflozin and silymarin alone showed moderate inflammation and structural alterations. These findings highlight the effect of dapagliflozin and silymarin, especially in combination, to mitigate cisplatin-induced nephrotoxicity by reducing oxidative stress, inflammation, and apoptosis via modulation of the Nrf2/HO-1 pathway.